NR4A1-3 nuclear receptor activity and immune cell dysregulation in rheumatic diseases - Murphy, Evelyn P.; Crean, Daniel (Frontiers in Medicine, 2022)
The development and progression of immune-mediated rheumatic disease (IMRD) involves dysfunction of innate and adaptive immune cell populations leading to altered responses including inflammasome activation, dysregulated cytokine networks, increased immune cell numbers and multifaceted cell-cell communication. Several rheumatic diseases are further characterized by the presence of autoantibodies, immune complex mediated complement activation and the deficit of peripheral immune tolerance due to reduced regulatory T-lymphocyte cell function. Ultimately in rheumatic disease the loss in cellular and tissue homeostasis culminates in the advancement of chronic inflammation. The three members of the NR4A subfamily of nuclear receptors are immediate early genes, and act as potent transcriptional responders to changes in the cellular and tissue microenvironment. Subfamily members are rapidly expressed in diseases characterized by inflammation and function to control the differentiation and activity of innate and adaptive immune cells in a cell-type and cell-context specific manner. Rheumatic disease including rheumatoid-, psoriatic-, osteoarthritis and systemic sclerosis display altered NR4A1-3 activity in controlling immune cell migration and function, production of paracrine signaling molecules, synovial tissue hyperplasia, and limiting cartilage turn-over in vivo. Additionally, NR4A1-3 activities mediate cytokine, prostanoid and growth factor signaling to control angiogenesis, modulate the regulatory functions of mesenchymal stromal cells, alter the activation status of dendritic cells, influence the generation of peripheral myeloid and T-lymphocyte lineages and promote the maintenance of functional regulatory T-cells. Further reports uncover the potential of moderating NR4A 1-3 receptors as therapeutic targets in altering immune tolerance, pathological angiogenesis and controlling inflammation in several models of disease.